Indonesian Language Learning Process Through Online System at SDN Class IV Muara Tiku Musirawas Utara - Murniyanto Murniyanto (Yayasan Literasi Kita Indonesia, 2021)
This research is looking at the current conditions that hit the whole world, namely the corona virus pandemic. A pandemic that causes the entire order of world life to change in all fields, one of which is in the field of education. Due to a pandemic, all activities outside the home are limited. Education is very important in life, therefore education must continue to be carried out during this pandemic. Schools during the pandemic are completed remotely or also known as web or internet learning. Distance learning interactions can maintain distance, and do not cause extreme sports outside the home, of course to maintain health. Furthermore, to find on the web or the internet the learning steps are well done. Exploration is subjective and the subjects of this test are educators and students of SDN class 1V Muara Tiku. The exam cycle begins with the perception to decide on the school's internet learning interactions. Further meetings and documentation. The information collected is checked using reports or explanations from educators and students. The achievement of learning with an online framework in Indonesian language learning includes (a) the use of whatsapp gatherings, (b) dramatization techniques and online conversations, (c) supporting elements for picking up network distances that must be steady and displaced using media, (d) inhibiting factors for interaction learning is an organization that is often disconnected from the network, the topics are difficult to understand.